Electronic Judiciary (E-Court) from the Perspective of Maslahah Theory and Its Correlation with the Realization of a Supreme Judicial Institution - Azis, Fitriah; Nugraha , Alfajar; Firdaos, Mochamad (ABHATS: Jurnal Islam Ulil Albab, 2025)
The advancement of information technology has significantly driven reform within Indonesia’s judicial system, particularly through the implementation of an electronic court system (e-Court). This article aims to analyze e-Court from the perspective of maslahah theory in Islamic law and to assess its contribution to the realization of a supreme and dignified judiciary. Employing a qualitative-descriptive approach through a literature review method, this study evaluates the relevance of maqāṣid al-sharī‘ah values in the e-Court system. The findings reveal that e-Court not only enhances administrative efficiency but also aligns with the core principles of Islamic law, such as the protection of life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), wealth (ḥifẓ al-māl), and religion (ḥifẓ al-dīn). During the pandemic, the role of e-Court evolved from serving a secondary need to becoming a primary necessity due to its function in safeguarding human existence. Therefore, the e-Court system can be regarded as a strategic instrument for supporting a judicial institution that is inclusive, adaptive, and oriented toward public benefit (maslahah). This study recommends strengthening the implementation of e-Court based on Islamic values to ensure comprehensive substantive justice for society. [Perkembangan teknologi informasi telah mendorong reformasi signifikan dalam sistem peradilan Indonesia, salah satunya melalui implementasi sistem peradilan elektronik (e-Court). Artikel ini bertujuan untuk menganalisis e-Court dari perspektif teori maslahah dalam hukum Islam dan menilai kontribusinya terhadap perwujudan lembaga peradilan yang agung. Penelitian ini menggunakan pendekatan kualitatif-deskriptif dengan metode studi pustaka untuk mengevaluasi relevansi nilai-nilai maqāṣid al-sharī‘ah dalam sistem e-Court. Hasil kajian menunjukkan bahwa e-Court tidak hanya efisien secara administratif, tetapi juga sejalan dengan prinsip-prinsip syariat, seperti perlindungan terhadap jiwa (hifẓ al-nafs), akal (hifẓ al-‘aql), harta (hifẓ al-māl), dan agama (hifẓ al-dīn). Dalam situasi pandemi, e-Court bahkan telah meningkat kedudukannya dari kebutuhan sekunder menjadi kebutuhan primer karena perannya dalam melindungi eksistensi manusia. Oleh karena itu, sistem e-Court dapat diposisikan sebagai instrumen strategis dalam mendukung lembaga peradilan yang inklusif, adaptif, dan maslahat. Penelitian ini merekomendasikan penguatan implementasi e-Court berbasis nilai-nilai keislaman guna memastikan keadilan substantif yang menyeluruh bagi masyarakat.]